The effects of CLIL on L1 and content learning: Updated empirical evidence from monolingual contexts. (October 2018) - Pérez Cañado, María Luisa
Abstract: This article reports on a quantitative study into the effects of CLIL programs on the L1 competence and content knowledge of Primary and Secondary Education students in monolingual contexts. It has worked with a sample of 2024 students in twelve monolingual provinces in Spain; has guaranteed the homogeneity of bilingual and non-bilingual groups in terms of motivation, verbal intelligence, and English level; and has factored in type of school, setting, and socioeconomic status as intervening variables. It has also carried out successive discriminant analyses in order to determine which variables are responsible for the differences ascertained. The results evince that CLIL is not detrimentally impacting L1 competence and is not watering down content learning, on which the positive impact of CLIL is particularly felt in the long term. The modulating effect exerted by the moderating variables considered is substantial for type of school and SES, but not for rural-urban setting. Highlights: CLIL is not detrimentally impacting L1 competence. CLIL is not watering down content learning in either Primary or Secondary Education. Public and private bilingual schools outstrip public and charter non-bilingual ones. The rural-urban divide is unsubstantial for CLIL learners. Students with a higher SES outperform those from a lower socioeconomic background.